Recent Status of Pests and Diseases on Cut Roses in Batu East Java - Handayati, Wahyu; Sihombing, Donald (KnE Life Sciences, 2017)
Rose is one of the most important ornamental plants in Indonesia. Almost 57.02% of the national cut rose’s demand was supplied from East Java, mainly from Batu. However, in the production process, there are various problems, especially pest and disease damages. In this regard, a study was conducted to determine recent status of the pests and diseases on roses in cultivation center of Batu, East Java. Observation was carried out in the farmers’ field randomly, from October to December 2014. Observation was performed on type and damage intensity of the pests and diseases. The pests and plant damage were sampled for further identification. An interview was made with some farmers to get secondary data about the type and the importance of the pests and diseases as well as the effort for controlling them. The result showed that some pests and diseases found included aphid, armored scale insect, spider mite, thrips, black spot, crown gall and powdery mildew. Based on morphological identification, there were two families of armored scale insect, i.e., Coccidae and Diaspidae. The highest damage intensity was due to armored scale insect, thrips, black spot and crown gall with the percentage of damage intensities of 50.50%, 20.00%, 45.50% and 65.00%, respectively. Based on those data, scale insect, thrips, black spot and crown gall were classified as important pests and diseases on roses in this area. Some pesticides and other materials like petroleum oil and detergent were used by the farmers to control either pests or diseases, but they were ineffective, especially in controlling armored scale insect and crown gall. Keywords: Cut roses, pest, disease, inventory, observation, status